Beauty Matters, Race Matters: Issues of Beauty in the African-American Family in The Bluest Eye and I Know Why the Caged Bird Sings - Carvalho, Ana Carolina Campos de (Em Tese, 2007)
This essay studies Toni Morrison’s The Bluest Eye and MayaAngelou’s I Know Why the Caged Bird Sings and the stories ofblack girls relating their color to the beauty standards set bywhite America. It shows the role families play on these girls’reaction to these standards.